Comparison of Perioperative Ranibizumab Injections for Diabetic Macular Edema in Patients Undergoing Cataract Surgery - Erhan Yumuşak; Kemal Örnek (Journal of Ophthalmology)
Purpose. To compare the efficacy of perioperative ranibizumab injections on diabetic macular edema (DME) in patients undergoing cataract surgery. Methods. This study included 59 eyes of 59 patients. All patients had advanced cataract with DME and underwent an uneventful phacoemulsification surgery. There were 3 subgroups. The first group received intravitreal ranibizumab injection 2 weeks preoperatively, the second group received intraoperatively, and the third group received 2 weeks postoperatively. Follow-up examinations were performed at 1 week as well as at 1 and 3 months. Results. Baseline visual acuity showed a significant increase in all groups at 1 month. In group 1, compared to baseline value, foveal thickness (FT) increased significantly at 1 month and showed a significant decrease up to month 3. In group 2, FT increased at month 1 and this continued up to month 3. In group 3, FT increased at month 1 and was almost stable up to month 3. There were not any significant differences for visual acuity and FT between the groups. Conclusions. Although intrapostoperative ranibizumab injection for DME seems to be more effective than preoperative injections in patients undergoing cataract surgery, the treatment still needs to be continued following surgery.